Method Of Using A Rheological Model In Studying The Process Of Compensation Of Subgrade Soils With A Vibrating Roller - Xankelov Tavbay Qarshievich; Komilov Samandar Iskandarovich; Hudaykulov Rashidbek Mansurjonovich; Musirov Makhmarajab Uralovich (Academia Open, 2025)
General Background: Effective soil compaction is fundamental to the stability and durability of road infrastructure, requiring accurate modeling of soil–machine interaction. Specific Background: Rheological models have become essential tools for describing elastic, viscous, and plastic behaviors that emerge when vibrating rollers interact with diverse soils, including saline subgrade materials. Knowledge Gap: Existing studies have not fully integrated multi-zone rheological behavior into a unified analytical model capable of characterizing deformation dynamics under real vibration loading. Aims: This study aims to develop an improved multi-mass rheological model that captures the elastic, viscous, and plastic responses of soils during roller compaction and to derive analytical expressions for predicting deformation characteristics. Results: The research presents a three-mass rheological system incorporating Hooke, Newton, and Saint-Venant elements, derives coupled differential equations for soil–roller interaction, and proposes closed-form static and dynamic solutions for displacement and vibration response. The model predicts system stability, resonance susceptibility, damping behavior, and deformation under varying excitation frequencies. Novelty: The study integrates soil layer properties into a multi-zone rheological framework, offering a more comprehensive representation of compaction mechanics than prior single-zone or simplified models. Implications: The findings provide a scientific basis for optimizing roller parameters, preventing resonance, improving compaction uniformity, and enhancing predictive simulations in road construction engineering.Highlight : The study explains how rheological models represent elastic, viscous, and plastic behavior during roller–soil interaction for more accurate compaction analysis. Various models—Hooke, Newton, Maxwell, Kelvin, and Bingham—are applied to describe soil deformation under dynamic loading. A three-mass rheological system is developed to predict vibration stability, resonance risk, and soil response during compaction. Keywords : Roadbed, Roller, Rheological Model, Elastic State, Saline Soil